So, You Want to Be a Better Educator …Review of: Three highly recommended online resources at academic teaching and learning centers: - Todd P. Primm (American Society for Microbiology, 2012)
Review of: Three highly recommended online resources at academic teaching and learning centers, including: The McGraw Center for Teaching and Learning at Princeton University, The Institute for Teaching, Learning, and Academic Leadership (ITLAL) at the University of Albany, and The Center for Teaching and Learning at the University of Minnesota.